Hubungan Dukungan Keluarga dengan Motivasi Remaja dalam Pencegahan Pernikahan Usia Dini di Kabupaten Karangasem - Ni Komang Ayu Juniari; I Kadek Nuryanto; Ni Komang Tri Agustini (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2024)
Introduction: Indonesia remains among the top 10 countries in the world for early marriage instances in 2022 with 1.74 million marriages. Family support is still a significant factor in the case of early marriage and plays a useful role in preventing early marriage for adolescents. Objective: The purpose of the study is to determine the correlation between family support and the motivation of adolescents in preventing early marriage at SMA Negeri 1 Abang Karangasem. Method: This study used analytic correlation with a cross-sectional approach. There were 253 respondents recruited as a sample of the study which was selected through a random sampling technique. The data were collected using the Perceived Social Support from Family (PSS-Fa) questionnaire and a motivation questionnaire. The data were analyzed using Spearman’s rho. Result: The finding showed that there was a correlation between family support and the motivation of adolescents in preventing early marriage with a p-value of 0.001 with a closeness of 0.382 and a positive correlation (+), which meant that the better the family support, the higher the motivation of adolescents in preventing early marriage. Conclusion: There is a correlation between family support and the motivation of adolescents in preventing early marriage at SMA Negeri 1 Abang Karangasem.